Representasi Unsur Kebudayaan Tionghoa dalam Film Animasi Turning Red (2022) - Wafa Nabila Syariva (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2025)
The representation of nation’s cultural elements can be portrayed through film. The film that portrays cultural elements is Turning Red, directed by Domee Shi and produced by Walt Disney and Pixar Animation. Based on that, this study aims to describe the elements of Chinese culture as reflected in the film Turning Red (2022). The theory used in this research is using Koentjaraningrat’s theory which divides into seven parts; 1) religious or belief system, 2) social system, 3) knowledge system, 4) language, 5) arts, 6) livelihood system, 7) life equipment and supplies. The types and methods of this research is using qualitative descriptive methods as the basis for the research. This research Charles Sanders Peirce’s theory of semiotics known as triadic triangles which divides signs based on symbols, objects, and interpretants. The data for this research collected from the film Turning Red and compiled in the form of cutout from scenes in the film.